PERIPHERAL BLOOD MONONUCLEAR DNA DAMAGE IDENTIFIED BY THE «СOMET» METHOD, AS A POSSIBLE INDICATOR OF SENSITIVITY OF MELANOMA TO IMMUNOTHERAPY WITH NIVOLUMAB - E. V. Tsyrlina; T. E. Poroshina; A. P. Oganesyan; S. A. Protsenko; L. M. Bershtein (Сибирский онкологический журнал, 2021)
Purpose of the study: to assess whether the determination of the grade of dNA damage in the blood lymphocytes of patients with metastatic melanoma can be a criterion for assessing the effectiveness of therapy. Material and Methods. The grade of dNA damage in blood mononuclear cells was studied using the comet assay in 10 patients with progressive metastatic melanoma before therapy with Nivolumab and 3–4 months after Nivolumab therapy. Results. It was revealed that prior to treatment the level of dNA damage in blood mononuclears was higher in patients with melanoma than in controls (healthy subjects). This level significantly decreased when stable disease or complete regression were reached, while it changed less significantly or increased in cases with disease progression. Сonclusion. The initial level and changes in lymphocyte dNA damage in patients with melanoma can serve as a criterion for assessing tumor  response to immunotherapy with Nivolumab.